Effects of sound stimuli on the phenotypic and genotypic characteristics of Staphylococcus aureus / Isma Syahril Ismail - Ismail, Isma Syahril (2016)
When listening to music, the ear is the closest organ to be exposed to sound. The external auditory canal of the ear is colonised by normal flora such as Staphylococcus aureus, which is inevitably exposed to sound waves. In an immunocompromised patient, a change in the equilibrium of the microflora would be detrimental. This study aims to determine whether S. aureus undergoes any phenotypic or genotypic changes after exposure to various types of sounds. S. aureus was exposed to sounds produced from two musical instruments i.e. acoustic and electrical; and solo vocalisation. A non-exposed group was included as a control. The bacteria in liquid medium were exposed to the sounds while incubating at 37°C. After nine hours of exposure to the various types of sound, the bacteria were evaluated for any changes in phenotypic and genotypic characteristics. Results showed that there was no change in the growth pattern of the bacteria although the growth rate was enhanced in all the exposed groups. However, there was no change in their morphology, biochemical properties and susceptibility to three antibiotics. The biofilm production of the bacteria increased following the exposure to all types of sound. Protein profile of the acoustic and electrical instrument groups showed a deletion of a 30 to 32 kDa protein but the nucleotide sequences of seven housekeeping genes of the bacteria were not altered. In conclusion, exposure of S. aureus to audible sounds produced by acoustic and electrical instruments, as well as solo vocalisation resulted in some changes in their biological characteristics.